Interstitial Spatiality and Subversive Sustainability: Urban Foraging in Ava Chin’s Eating Wildly and Rita Wong’s forage - He, Yiyi (Journal of Ecohumanism, 2022)
I apply political ecologist Ryan Galt’s concept of ‘subversive and interstitial food spaces’ (Galt et al., 2014, 133) to read Chinese American writer Ava Chin’s semi-autobiographical memoir, Eating Wildly (2014), and Chinese Canadian writer Rita Wong’s poem collection, forage (2007). Beyond offering a different cultural perspective, I argue that Chin’s and Wong’s urban foraging narratives can be read as transitioning from being interstitial to subversive in the North American context. I see urban spaces where plants are foraged but not normally considered to be cultivatable as interstitial. Analogously, I regard people situated between cultures or on the margins of dominant spaces due to their race or class as being in an interstitial position. Echoing ancient East Asian and specifically Chinese environmental thinking, which is relational, non-linear, and non-dichotomous, Chin’s and Wong’s foraging discourses in their poetic, eth(n)ic, and environmental complexities challenge dominant white foraging narratives and provide alternatives to mainstream environmental thinking. Both urban foraging experiences depicted in Eating Wildly and forage thrive from interstitial spatiality, yet they direct us toward subversive and sustainable foodways that promotes food justice and dismantles rural-urban, local-global, human-nature binaries. I will also highlight how the two authors differ in their foraging poetics and politics.